2013
DOI: 10.1021/ef400330j
|View full text |Cite
|
Sign up to set email alerts
|

Density of Hydrocarbon Mixtures and Bitumen Diluted with Solvents and Dissolved Gases

Abstract: Density data are reported for the following mixtures at temperatures from 20 to 175 °C and pressures up to 40 MPa: ethane + n-decane, propane + n-decane, butane + n-decane, propane + toluene, and propane + cyclooctane, as well as bitumen diluted with ethane, propane, n-butane, n-pentane, n-heptane, and carbon dioxide. A straightforward excess volume based mixing rule is proposed to determine the density of liquid mixtures of hydrocarbons. Excess volumes are accounted for with a binary interaction parameter, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 51 publications
2
53
0
Order By: Relevance
“…The average absolute percent deviation between the interpolated mixture density data obtained in this study from the data reported by Reamer and Sage is 0.7% for $344 K, 0.9% for $444 K, and 1.2% for $510 K isotherm. Although not shown here, the (C 3 + C 10 ) mixture density data are also in good agreement with the limited data reported to 40 MPa for three compositions by Saryazdi et al [6]. As an example, the average absolute percent deviation between data obtained in this study at x 1 = 0.1597 for 444 K and the data reported by Saryazdi and coworker at x 1 = 0.17 for 448 K is within 1.1%.…”
Section: Table 1asupporting
confidence: 92%
See 1 more Smart Citation
“…The average absolute percent deviation between the interpolated mixture density data obtained in this study from the data reported by Reamer and Sage is 0.7% for $344 K, 0.9% for $444 K, and 1.2% for $510 K isotherm. Although not shown here, the (C 3 + C 10 ) mixture density data are also in good agreement with the limited data reported to 40 MPa for three compositions by Saryazdi et al [6]. As an example, the average absolute percent deviation between data obtained in this study at x 1 = 0.1597 for 444 K and the data reported by Saryazdi and coworker at x 1 = 0.17 for 448 K is within 1.1%.…”
Section: Table 1asupporting
confidence: 92%
“…The present study reports high-temperature, high-pressure, (HTHP) density data for propane mixtures with n-decane or n-eicosane at several compositions. Data on propane mixtures with n-octane [5] and n-decane [6] have recently been reported but only at maximum pressures to 40 MPa and temperatures to 448 K, which are below HTHP conditions. However, the propane-n-decane (C 3 + C 10 ) model system was studied in some broader detail and was reported by Reamer and Sage in 1966 [7] for nine mixture compositions, at temperatures to 513 K, but only at pressures to 70 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of asphaltene precipitation and asphaltene yield have been evaluated experimentally by Akbarzadeh et al [10] and Wiehe et al [11]. Recently, Saryazdi et al [12] measured the density of n-heptane/bitumen mixtures at two different concentrations (15 and 30 weight percent) over temperature and pressure ranges, 20-175°C and 0.1-10 MPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical correlations have been used in reservoir simulators to predict the viscosity behavior of petroleum fluids which are generally treated as single components; for example, the Walther correlation (Walther, 1931), the Vogel correlation (Vogel, 1921), and the Andrade correlation (Andrade, 1934). These correlations are intended for single-phase liquids far from their critical point (Yarranton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mehrotra (1991) presented a set of logarithmic mixing rules to calculate the viscosity of mixtures bitumen-solvent as a function of the mole fraction, molecular weight, and a temperature dependent binary interaction parameter. Yarranton et al (2013) developed mass fraction based mixing rules for the Walther correlation applicable to dead and live conventional oils and bitumens diluted with solvents over a broad range of temperatures and pressures. This approach is promising for liquid conditions, including diluted bitumens far from the critical point, but does not encompass the entire phase diagram.…”
Section: Introductionmentioning
confidence: 99%